Are metabolic syndrome and its components associated with 5-year mortality in chronic obstructive pupmonary disease patients? - Tanni, Suzana Erico [UNESP]; Zamuner, Amanda T. S. [UNESP]; Coelho, Liana S. [UNESP]; Vale, Simone A. [UNESP]; Godoy, Irma [UNESP]; Paiva, Sergio A. R. [UNESP] (Mary Ann Liebert, Inc, 2015)
The aim of this study was to evaluate the risk of mortality according to the presence of metabolic syndrome in chronic obstructive pulmonary disease (COPD) patients who were followed for 5 years. We did not establish the influence of metabolic syndrome on mortality rate. However, an increase of 100 mg of triglycerides was associated with a 39% increase in the probability of death in the period of the study (hazard ratio 1.39, 95% confidence interval 1.06-1.83).